Pengetahuan ibu tentang pemilihan alat kontrasepsi - Poniyah Simanullang; Selli Dosriani Sitopu; Ester Mei Prida Girsang; Yunisa Hulu (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Indonesia is one of the countries with the highest population growth in the world. In an effort to reduce the birth rate, the government has implemented a mandatory family planning program for couples of childbearing age. This program not only reduces the birth rate but also improves maternal and child health. There are various contraceptive methods available. Family planning participants are given the freedom to choose the contraceptive method most appropriate for their individual circumstances. Purpose: To describe the extent of mothers' knowledge regarding contraceptive selection. Method: Descriptive design. All 120 women of childbearing age who accepted family planning constituted the study population. A total of 30 were sampled using accidental sampling. Results: 22 (73.3%) were categorized as lacking knowledge. This lack of knowledge impacts the community's limited ability to understand the importance of accepting family planning as an effort to reduce birth rates and improve maternal and child health. Conclusion: Contraceptive selection is not appropriate based on the number of children and age of women of childbearing age. Suggestion: Respondents are encouraged to seek information about long-term contraception. In order to conduct research to analyze the factors that influence the choice of contraceptives